2003
DOI: 10.1046/j.1365-2036.18.s1.20.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rebamipide, a gastro‐protective drug on the Helicobacter pylori status and inflammation in the gastric mucosa of patients with gastric ulcer: a randomized double‐blind placebo‐controlled multicentre trial

Abstract: SUMMARYAims: To investigate the effects of rebamipide on the Helicobacter pylori eradication rate with amoxicillin and omeprazole. The trial also examined its histological effects on gastro-mucosal inflammation after eradication. Methods: Two hundred and six H. pylori-positive patients with active gastric ulcer underwent 8-week based therapy (OA) consisting of 2-week amoxicillin with omeprazole and subsequent 6-week omeprazole. They randomly received either rebamipide (OA-R) or placebo (OA-P) for 16 weeks: com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
(35 reference statements)
0
18
0
1
Order By: Relevance
“…A number of studies have shown that rebamipide, a gastroprotective agent, is effective for the treatment and prevention of gastric ulceration and mucosal damage in vivo (8,(10)(11)(12)(13)(16)(17)(18)(19). Although some reports revealed the molecular mechanism underlying the protective effect of rebamipide in vitro (14,22,23), the precise mechanism remains to be identified.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of studies have shown that rebamipide, a gastroprotective agent, is effective for the treatment and prevention of gastric ulceration and mucosal damage in vivo (8,(10)(11)(12)(13)(16)(17)(18)(19). Although some reports revealed the molecular mechanism underlying the protective effect of rebamipide in vitro (14,22,23), the precise mechanism remains to be identified.…”
Section: Discussionmentioning
confidence: 96%
“…Clinically, a randomized double-blind controlled study revealed that the use of rebamipide resulted in a marked decrease in inflammation in the gastric mucosa (11). Rebamipide accelerated healing and reduced re-lapse of acetic acidinduced gastric ulcer in rats (12).…”
mentioning
confidence: 99%
“…Preclinical data has demonstrated various mechanisms involved in rebamipide effects on H. pylori-associated gastritis, including disturbance of the adhesion of H. pylori to gastric epithelial cells and inhibitory effects on H. pylori-induced neutrophil activation or interleukin-8 secretion [6][7][8]. A few reports have even suggested that rebamipide may have a potential anti-H. pylori role [9] while this was not confirmed in large clinical trials [10]. However, we still lack clinical data on rebamipide for the treatment of H. pylori-related gastritis.…”
mentioning
confidence: 94%
“…Kim et al [137] observed as it altered the infl ammatory response in human gastric epithelial cell lines infected with CagA+ H. pylori , inhibiting the activation of NF-B and in turn blocked both the transcription and expression of the IL-8 gene. Similarly, rebamipide which displays anti-infl ammatory gastric properties and stimulates the synthesis of endogenous prostaglandins in the gastric mucosa [138] , was shown to be capable of reducing mucosal infl ammation even in the absence of H. pylori eradication [139] . Both these drugs therefore represent potential candidates as add-on medication to eradication regimens.…”
Section: Rescue Therapies After Two or More Failuresmentioning
confidence: 99%